MAKNA KULTURAL DAN SOSIAL-EKONOMI TRADISI SYAWALAN - Anwar, Khoirul (WALISONGO, 2013)
AbstractThis article tries to uncover the cultural reason on Syawalan tradition in the villageof Morodemak in Bonang, Demak. It also intends to reveal the meaning of thetradition for todayâs society. Observations, interviews and examination of secondarydata, can be conluded that the tradition of Syawalan in Morodemak is one oftraditions that expresses the religious Javanese culture in coastal area. ForMorodemak community, tradition of Syawalan is a form of gratitude to GodAlmighty for the gift of the abundance of seafood as well as an expression of prayerfrom dangerous things in life that can arise from the sea. Syawalan tradition also hasthe meaning of caring for nature, especially the sea as well as the meaning ofcohesion and communality among fishing communities. In addition to the culturalmeanings, traditions Syawalan also have economic and socio-cultural significancefor the local governments and communities.***Tulisan ini berusaha untuk mengungkap nalar kebudayaan pada tradisi Syawalandi Desa Morodemak Bonang Demak. Selain itu juga bermaksud mengungkapmakna tradisi tersebut bagi masyarakat saat ini. Hasil pengamatan, wawancaraserta telaah terhadap data sekunder, dapat dijelaskan bahwa tradisi Syawalan diMorodemak merupakan salah satu tradisi masyarakat yang mengekspresikankebudayaan masyarakat Jawa pesisiran yang religius. Bagi masyarakatMorodemak, tradisi Syawalan merupakan wujud rasa syukur pada Tuhan YMEatas karunia melimpahnya hasil laut sekaligus ungkapan doa keselamatan darisegala mara-bahaya yang bisa timbul dari laut. Tradisi Syawalan juga memilikimakna kepedulian kepada alam, khususnya laut serta makna membangunkerukunan dan keguyuban di antara masyarakat nelayan. Selain makna-maknakultural tersebut, tradisi Syawalan juga memiliki makna ekonomis dan sosialbudaya bagi pemerintah lokal dan masyarakat.Keywords: tradisi Syawalan, makna kultural, makna sosial ekonomi